Respon Konsumen Terhadap Online Grocery Mobile Application Melalui S-O-R Model - Noel, Christinne Yvonne; Saphira, Justine; Istijanto, Istijanto; Realino, Bernardinus (Universitas Prasetiya Mulya, 2024)
Since Covid-19, there has been a shift in behavior and an increase in users transitioning from offline to online grocery shopping. Online grocery is part of e-commerce, where users mostly access it through mobile shopping applications or mobile commerce, which offer numerous benefits to users. This research aims to identify the factors that influence repurchase intention and satisfying experience in online grocery mobile applications. The theory used in this study is the S-O-R (Stimulus Organism Response) model by Mehrabian and Russel (1974), analyzed using Structural Model Equation (SEM). The findings of this research indicate that impulsiveness is highly influenced by app incentives, while perceived value is greatly influenced by perceived ubiquity. Furthermore, both repurchase intention and satisfying experience are more influenced by perceived value than impulsiveness. The study provides several implications that can be applied to optimize the development of online grocery mobile applications.